If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(x + -4) = 0 Reorder the terms: y(-4 + x) = 0 (-4 * y + x * y) = 0 Reorder the terms: (xy + -4y) = 0 (xy + -4y) = 0 Solving xy + -4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. xy + -4y + 4y = 0 + 4y Combine like terms: -4y + 4y = 0 xy + 0 = 0 + 4y xy = 0 + 4y Remove the zero: xy = 4y Divide each side by 'y'. x = 4 Simplifying x = 4
| 9=-2z+3 | | 2n^2+9n+7=0 | | 9+3x=21+3 | | m-(-5)=7 | | p*h=4m | | -3x/5+1=5/12 | | 8(6-7x)=104 | | -8=n/3-10 | | 12-2k=k-7+7 | | 20w+-15w+-17=18 | | 2z+11=65-4x | | y=0.001x^2+0.3x | | 6(f+5)=2f+8 | | xy+3= | | k/72=0.8 | | 8(1-5n)+8n=200 | | 13.1=h+6.2 | | -6+25=m-10 | | -12=p-2 | | -2(5k-3)=86 | | 170m=1.54 | | -55x-20=0 | | 6+2p=10 | | 2c^2+5c+2=0 | | 3x-12+6=0 | | 170=1.54 | | 8a+3a=132 | | 18-b=13 | | 1-2/3y=12/5-1y/5 | | 7c+2c-8c=17 | | 8(1+5x)=-312 | | 3(3+5x)=2/3+3/7x |